2013
DOI: 10.1371/journal.ppat.1003570
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Migration and Persistence in North American Wild Birds

Abstract: Wild birds have been implicated in the emergence of human and livestock influenza. The successful prediction of viral spread and disease emergence, as well as formulation of preparedness plans have been hampered by a critical lack of knowledge of viral movements between different host populations. The patterns of viral spread and subsequent risk posed by wild bird viruses therefore remain unpredictable. Here we analyze genomic data, including 287 newly sequenced avian influenza A virus (AIV) samples isolated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
110
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 43 publications
7
110
0
Order By: Relevance
“…Similarly, the HA and NA genes of AIVs in Argentina differ from those of viruses circulating in North America and Eurasia 13. The main subtypes of AIV consistently reported to circulate in other countries14, 15, 16, 17, 18, 19 have not been reported in Brazil. However, an H11N9 influenza virus was recently identified for the first time in South American migratory birds in the Amazon region, and this virus showed great similarity to viruses of North American, rather than South American, lineages 20…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, the HA and NA genes of AIVs in Argentina differ from those of viruses circulating in North America and Eurasia 13. The main subtypes of AIV consistently reported to circulate in other countries14, 15, 16, 17, 18, 19 have not been reported in Brazil. However, an H11N9 influenza virus was recently identified for the first time in South American migratory birds in the Amazon region, and this virus showed great similarity to viruses of North American, rather than South American, lineages 20…”
Section: Introductionmentioning
confidence: 98%
“…In fact, these mallards were captured for surveillance for influenza in 2001, and analysis of data between 2001 and 2006 reveals that 16.6% of Alberta ducks are influenza carriers (68). Alberta is the convergence point for four major North American flyways, and the majority of genetic diversity observed in the influenza gene pool has been recovered over time in Alberta (69). We might predict that pressure from duck CD8 + T cell immunity and viral escape is partially responsible for diversity of viral proteins, just as Ab responses to hemagglutinin may explain prevalence of multiple viral subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even though we followed bird populations as they migrated down the river, due to the high levels of reassortment in AIV, we recovered only four isolates containing the same virus constellations. Studies investigating North American AIV movement over much broader geographic and temporal scales suggested that the initial movement of AIVs is likely to occur along migratory routes, but these studies were limited by the availability of surveillance samples from these flyways and may have underestimated the amount of movement occurring within the flyways themselves (19,20). The present study provides empirical evidence suggesting that waterfowl in the MMF disperse AIV genetic diversity quickly within the migratory corridor and that surveillance efforts to detect AIV threats to human and domestic animal health should pay particular attention to these routes in initially responding to epidemics/epizootics.…”
Section: Discussionmentioning
confidence: 99%
“…LPAIVs in the MMF. Studies have shown that LPAIVs can be genetically structured within and between North American migratory flyways (20,35,45,46), even in light of relatively high levels of gene flow measured between flyways (19). In the present study, while we observed a pattern of increased dispersal of AIVs within the MMF over short time frames, we also observed signatures of regional persistence of gene diversity across multiple sea- sons, which suggests a temporal effect on the genetic structuring of AIV diversity both within and among flyways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation